A Meta Heuristic Approach For Efficient Route Recovery In Mobile Ad Hoc Networks - et al., Patnala Satish Kumar (International Journal of Advanced Science and Technology, 2019)
Routing is a complex issue in Mobile Ad hoc Networks (MANET) due to its dynamic and frequently changing network topology. Route failures, packet collision, bad channel condition and congestion are to be considered while designing reliable routing protocol in MANET, since these factors tends to increase the packet loss and degrade the bandwidth and battery power. Reliable routing protocols for mobile ad hoc networks use many link reliability metrics for finding these links; four of the most commonly used are “Link Expiration Time”, “Link Received Signal Strength”, “Residual Energy” and “Available Bandwidth”. It is shown that these metrics enhance the reliability and reduce the number of route reconstructions. However, minimization of Packet loss, Communication overhead  are a challenging task to improve the performance. This paper  addresses the  finding of optimal path by predicting node , link lifetime using a  meta heuristic algorithm called modified cuckoo search  algorithm.